2016
DOI: 10.1002/jbm.a.35756
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a patterned hydrogel—fibrous mat bilayer structure to mimic choroid and Bruch's membrane layers of retina

Abstract: Deterioration of retina and death of the retinal cells due to age, diabetes, or occlusion can cause retinal degeneration which leads to loss of vision. In this study, it is aimed to design a bilayered matrix to mimic the choroid and the Bruch's membrane of the retinal tissue. As choroid, a microchanneled network resembling a fractal tree design was fabricated by photolithography over photo-cross-linkable methacrylated hyaluronic acid hydrogel. Gelatin or collagen was immobilized into the microchannels to enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…The biocompatibility of this BCN hydrogel has previously been confirmed both in vitro and in vivo in the chick embryo. Literature data has also repeatedly confirmed the biocompatibility of both gelatin and hyaluronic acid . In this study, we used HDFs as model cells to test if the material supported their attachment and proliferation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The biocompatibility of this BCN hydrogel has previously been confirmed both in vitro and in vivo in the chick embryo. Literature data has also repeatedly confirmed the biocompatibility of both gelatin and hyaluronic acid . In this study, we used HDFs as model cells to test if the material supported their attachment and proliferation.…”
Section: Discussionmentioning
confidence: 94%
“…Literature data has also repeatedly confirmed the biocompatibility of both gelatin and hyaluronic acid. 19,20 In this study, we used HDFs as model cells to test if the material supported their attachment and proliferation. We demonstrated that Micrographs of the control and estradiol-releasing hydrogels taken on day 14 of embryonic development demonstrate a significant increase in the mean vessels count with estradiol-releasing hydrogels compared with the controls (n = 6 for each group) HDFs produced significantly more ECM when grown on the estradiol-releasing hydrogels as compared with plain hydrogels.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, it was believed that scaffolds simulated the extracellular matrix (EMC) in the regeneration of retina, and served as a support for cell migration, adhesion, and morphology only [16][17][18]. Emphasis was on loaded materials and morphology construction to develop biocompatible and biodegradable scaffolds with appropriate mechanical properties [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Collagen type I was isolated from Sprague-Dawley rat tails as described by earlier studies. (20,21) For the isolation steps, briefly, tendons from rat tails were dissolved in cold acetic acid (0.5 ᴍ), filtered, dialyzed against phosphate buffer, and centrifuged. The collagen pellet was dissolved in acetic acid (0.15 ᴍ), precipitated with NaCl solution (5% w.v -1 ), dialysis and centrifugation steps were repeated.…”
Section: Introductionmentioning
confidence: 99%